Mycological stability of minimally-processed young coconut (Cocos nucifera L.) as influenced by different chemical and physical treatments - Waje, C.K.; Dizon, E. I.; Serrano, E.P.; Mabesa, R. C. (2005)
The effect of different chemical and physical treatments on the mycological stability of minimally-processed young coconut (Cocos nucifera L.) was evaluated. Young coconuts were minimally-processed and dipped in sodium metabisulfite (5% and 10%), citric acid (2.5% and 5%), oxalic acid (2.5% and 5%) and hydrochloric acid (0.01%) solutions, and in hot water (50 C, 70 C and 100 C). Samples were stored under ambient room (25 C) and refrigerated (13 C) temperatures. Among the treatments used, only sodium metabisulfite was effective in prolonging the storage life of tender nuts in terms of preventing husk discoloration and surface mold growth. Under cold storage, surface mold growth was observed only after 4 wk. At ambient room temperature, maximum shelf-life is 3 d and 2 wk for the coconuts treated with 5% and 10% sodium metabisulfite, respectively. Samples treated with citric acid exhibited peel discoloration after 3 d under ambient and cold storage. For the nuts treated with oxalic acid, browning occurred at the 4th and 7th d under ambient and refrigerated temperatures, respectively. Peeled nuts dipped in hot water and hydrochloric acid readily turned brown after dipping. Seven representative mold isolates were isolated from tender nut samples. Cultural and morphological characteristics showed the identity of the mold isolates as Aspergillus niger, Penicillium citrinum, Syncephalastrum racemosum, Geotrichum candidum, Penicillium funiculosum, Penicillium islandicum and Helmintosporium curvulum. A. niger and P. citrinum were the most predominant.
Keywords: Coconut; Molds (Fungi)